2019
DOI: 10.1002/acn3.767
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of early cognitive dysfunction in Parkinson's disease

Abstract: Objective Dementia is a common and feared aspect of Parkinson's disease but there are no robust predictors of cognitive outcome. Visuoperceptual deficits are linked to risk of dementia in Parkinson's disease but whether they predict cognitive change is not known, and the neural substrates of visuoperceptual dysfunction in Parkinson's have not yet been identified. Methods We compared patients with Parkinson's disease and unaffected controls who underwent BO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…Recently, risk algorithms combined clinical information to predict cognitive change over time 23. Visual changes are also emerging as early markers of cognitive change in PD 24. Whether structural brain changes are more strongly linked with clinical risk scores or visual deficits before onset of dementia is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, risk algorithms combined clinical information to predict cognitive change over time 23. Visual changes are also emerging as early markers of cognitive change in PD 24. Whether structural brain changes are more strongly linked with clinical risk scores or visual deficits before onset of dementia is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that visuoperceptual deficits are an early indicator of PD dementia, 1 and we have previously shown that visuoperceptual deficits are linked to cognitive decline after 1 year. 6 By examining the differences in white matter connectivity in patients with PD and low visual performance and using a novel, more sensitive technique, we have highlighted additional white matter tracts that are affected in the earliest stages of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also in keeping with other neuroimaging studies highlighting the importance of connectivity changes in early cognitive impairment of PD. Changes in functional connectivity between visuospatial and frontal regions 42 and between the posterior cingulate with frontal regions 6,42 are seen in patients with PD and early cognitive impairment. We have also shown changes within the left fronto-occipital fasciculus, an association tract thought to play a role in executive function, semantic language, and visual processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations